2018
DOI: 10.1108/jhom-05-2018-0133
|View full text |Cite
|
Sign up to set email alerts
|

Darzi Clinical Leadership Fellows: an activity theory perspective

Abstract: Purpose The purpose of this paper is to review the impact of the clinical leadership programme, in enabling the Darzi fellows to lead change projects in health and care services, and to secure quality healthcare in the NHS beyond the lifetime of the programme. Design/methodology/approach A longitudinal empirical investigation of clinical leaders (n=80) over an eight-year period was framed through an activity theory (AT)-driven research methodology using a mixed-methods approach. Findings AT illuminated how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…The analysis of our empirical data from our evaluation of seven cohorts of the Chief Residents’ Clinical Leadership and Management programme Leadership and Management programme in the East of England suggested five outcome constructs for clinical leadership professional development, which we termed: Self‐efficacy, Engaging stakeholders, Boundary‐crossing expertise, Agency, and Willingness to take risks and to learn from risks and failures . We note that, as illustrated in Table 1, our review of analyses of other NHS clinical leadership development programmes (while often more descriptive, and less clearly theoretically framed that ours) showed those have identified several similar phenomena 36,74‐76 . This lends further support to the theoretical generalisability of our constructs which enrich and offer conceptual and operational specificity to findings from earlier empirical work on the outcomes of clinical leadership development which highlighted knowledge and attitudes regarding leadership and working with others.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The analysis of our empirical data from our evaluation of seven cohorts of the Chief Residents’ Clinical Leadership and Management programme Leadership and Management programme in the East of England suggested five outcome constructs for clinical leadership professional development, which we termed: Self‐efficacy, Engaging stakeholders, Boundary‐crossing expertise, Agency, and Willingness to take risks and to learn from risks and failures . We note that, as illustrated in Table 1, our review of analyses of other NHS clinical leadership development programmes (while often more descriptive, and less clearly theoretically framed that ours) showed those have identified several similar phenomena 36,74‐76 . This lends further support to the theoretical generalisability of our constructs which enrich and offer conceptual and operational specificity to findings from earlier empirical work on the outcomes of clinical leadership development which highlighted knowledge and attitudes regarding leadership and working with others.…”
Section: Discussionsupporting
confidence: 64%
“…We then present an original content analysis of selected UK clinical leadership policy documents to identify desired outcomes for clinical leadership development. Finally, we present the empirical findings from a systematic, mixed‐methods evaluation of a clinical leadership development programme (one of the first of its kind 36 ) to analyse its outcomes in practice. Based on an analytical synthesis of these, we develop a conceptual and operational model of clinical leadership, and the mechanisms by which it may be linked with desired organisational outcomes.…”
Section: Introduction: Challenges In Researching the Effectiveness Ofmentioning
confidence: 99%
“…The perception of outdoor thermal comfort in Malaysia also confirmed the value of PET in the selected shaded outdoor spaces was higher than the comfort range defined for tropical climates. This value was more than 30°C (Makaremi et al, 2012). Thus, it is recommended that a mixture of high-rise towers and lower buildings can create uneven fabric, which then increases air movement in a warm climate (Evans & De Schiller, 1996;Fanger & Toftum, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49][50][51] Most fellowships include a funded formal "taught" component (some of which are award bearing programs such as a postgraduate certificate), an internship with one or more senior healthcare leaders, and a range of experiential learning including visits to other organizations, networking events and conference attendance. 52 Fellowships often require taking one or more years out of program however, and can negatively impact on the Fellows' return to training, with a significant mind-set adjustment required after working out of program with senior leaders in non-clinical environments, and then going back to being simply "one of many" trainees. Despite the evidence that medical leadership and engagement improves outcomes and performance, 53 Fellows have reported that often clinicians do not understand what they have been doing on their fellowship and how they could subsequently use their new skills to engage in service and quality improvements', with some reporting indifference, even hostility towards them.…”
Section: Academic Careers In Leadership and Managementmentioning
confidence: 99%